Enhancing the Yield of Mature Olive Trees via Comparative Fertilization Strategies, including a Foliar Application with Fulvic and Humic Acids, in Non-Irrigated Orchards with Calcareous and Non-Calcareous Soils - Stavros Sotiropoulos; Christos Chatzissavvidis; Ioannis E. Papadakis; Victor Kavvadias; Christos Paschalidis; Chrysovalantou Antonopoulou; Sotirios Kiriakopoulos (Horticulturae, 2024)
This study investigated the impact of fertilization treatments on mature, forty-year-old, fully productive olive trees (Olea europaea L. cv. Koroneiki) in two non-irrigated orchards featuring contrasting soil types: non-calcareous–acidic and calcareous–alkaline. Over three years (2019–2021), seven distinct treatments were applied, involving inorganic soil fertilizers (traditional strategy) and foliar applications of a liquid organic product containing fulvic and humic acids. Fertilization significantly influenced physiological parameters, such as mineral nutrition, photosynthetic pigments of olive leaves, fruit yield, and oil production per tree, revealing noteworthy effects influenced by soil types and their interactions with treatments. Statistical analysis highlighted specific treatments, indicating that the foliar application of the organic product once a year in alkaline soil or biannually in acidic soil resulted in the highest observed fruit yield and oil production per tree. Indeed, contrary to the control–unfertilized trees, specific fertilization strategies resulted in an average increase of up to 47% and 73% in fruit yield per tree and up to 96% and 100% in oil production per tree in acidic and alkaline soil, respectively. Furthermore, consistently high yields were correlated with constant high values of the chlorophyll a/chlorophyll b ratio (2.3–3.3 in August for acidic soil) and leaf chlorophyll a concentration (55–66 mg/100 g f.w. in August for alkaline soil). This novel finding underscores the crucial role of these factors as prerequisites for achieving superior fruit production. Our results emphasize the potential of integrating foliar organic fertilization as a complementary strategy to traditional soil-based approaches. This is particularly relevant under non-irrigated/rainfed cultural conditions, emphasizing the significance of considering alternative fertilization practices for optimized olive orchard management.